Strange attractors - Sleator, William (New York : Dutton, 1990)
Max finds himself in possession of a time travel device which is eagerly sought by two desperate men, the scientist who invented it and the scientist's alter ego from a different timeline.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
6.2
5-8
Keywords: Science fiction; Time travel -- Fiction; Science fiction; Space and time -- Fiction